Platelet Release Reaction in vivo in Patients with Ischaemic Heart Disease after Isometric Exercise and its Prevention with Dipyridamole - Sano, Tadahiro; Motomiya, Takeshi; Yamazaki, Hiroh (Thrombosis and Haemostasis, 1979)
In 20 patients with ischaemic heart disease (IHD), platelet sensitivity to ADP- aggregation, plasma von Willebrand factor (vWF) and plasma β-thromboglobulin (β-TG) were measured before and after isometric exercise. Effect of dipyridamole on these determinants was studied in a crossover fashion. To assess plasma vWF level, a new simple method was employed which has the advantage of not requiring an optical aggregometer and was proved to be reproducible.No significant difference was seen in platelet sensitivity to ADP-aggregation, vWF and β-TG among healthy controls, IHD patients on placebo and on dipyridamole at rest. After exercise, platelet sensitivity to aggregation, plasma vWF and β-TG increased significantly in IHD patients on placebo. In healthy controls, no significant changes were seen. On dipyridamole, above changes seen in IHD patients were not seen.The results suggests that isometric exercise may induce platelet release reaction in vivo and may produce hypercoagulable state in IHD patients. These phenomena may be prevented by pretreatment with dipyridamole.